PENGARUH KEPEMIMPINAN TERHADAP KINERJA PEGAWAI MELALUI MOTIVASI SEBAGAI INTERVENING PADA BADAN PUSAT STATISTIK (BPS) KOTA KENDARI - Rinto Rinto; Nasrul Nasrul; Sriwiyati Mahrani (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2017)
This study aimed to find out the effect of leadership on working motivation, leadership on the staff’s performance, working motivation on staff’s performance, and leadership on the staff’s performance through working motivation as an intervening variable at the Central Bureau of Statistics (BPS) Of Kendari City.Population of the study were 26 people which included all staff of the Central Bureau of Statistics (BPS) Of Kendari City. Sample were determined using total sampling since the population was less than 100 so all of the population became the samples of the study. Data were analyzed using the Path Analysis of the Partial Least Square (PLS) Program.Results of the study showed the leadership had a positively significant effect on the working motivation at the Central Bureau of Statistics (BPS) Of Kendari City, leadership had a positively significant effect on the performance of staff at the Central Bureau of Statistics (BPS) Of Kendari City, working motivation had a positively significant effect on the performance of staff at the Central Bureau of Statistics (BPS) Of Kendari City, and leadership had a positively significant effect on the performance of staff through working motivation as an intervening variable at the Central Bureau of Statistics (BPS) Of Kendari City.